Effectiveness of Behavioral Counseling Theory with Lesson Study Through Modeling Techniques to Improve The Nature of Sympathy and Empathy Class Second Grade MIA 8 SMA Negeri 1 Denpasar - I Gusti Ngurah Adi Mahendra; I Ketut Dharsana; Ni Ketut Suarni (International Conference on Technology and Educational Science)
This research is a quasi research ("Quasi Experiment"). The purpose of this study was to Determine the effectiveness of modeling and sociodrama behavioral counseling techniques in self-assurance models for students of class XI MIA 8. The process of collecting the data in this study used observation sheets, interview sheets, diaries and self-assurance questionnaires. t-test. The results of this study experimental group treated with modeling techniques indicator 3 produces Tcount = 2.18> Ttable = 1,994. From this study and sociodrama effective modeling techniques to Improve The Nature Of Sympathy And Empathy students of class XI MIA 8 in SMA 1 Denpasar